Studi Kasus Skisma antar Denominasi Gereja Di Desa Parumpanai Dusun Rende-Rende Kabupaten Luwu Timur - Yohanis Yance Tandi Rerung; Agung Jaya; Daud Patana (Jurnal Amanat Agung, 2022)
Schism is a division that comes from within the church because of problems and differences that cannot be managed properly. The differences come from certain people who have different understandings of the Bible and make new interpretations that have an impact on divisions in society. The author discusses this topic to find out the impact of inter-denominational schism in people's lives in fellowship in various church denominations in Rende hamlet. -render. To find out what the effects of the inter-denominational schism are in the hamlet of Rende-rende, the author uses a qualitative research method with an intrinsic case study research approach so that the author can collect more in-depth data. Based on the results of the study, it was found that the impact of the schism between church denominations was that many Rende-rende community members were inconsistent in settling in a congregation, which was also accompanied by divorce in the family due to differences in church denominations in a household. Based on the results of this study, it was found that the church in Rende-rende hamlet was less united in maintaining unity among God's people.